Critical transformation pathways and socio-environmental benefits of energy substitution using a LEAP scenario modeling. (January 2021) - Yang, Dewei; Liu, Dandan; Huang, Anmin; Lin, Jianyi; Xu, Lingxing
Abstract: A successful transformation from conventional to renewable energy can contribute to climate change mitigation and regional development. As the co-host city of the 2022 Winter Olympic Games and the only National Renewable Energy Demonstration Zone in China, Zhangjiakou urgently needs to transform its conventional energy-dependent industries. This paper establishes a Long-range Energy Alternatives Planning System (LEAP)-Zhang model to examine the environmental and socio-economic effects of renewable energy development in Zhangjiakou by projecting the energy consumption and associated greenhouse gas emissions by various sectors over the 2016–2050 period. Two scenarios are designed, i.e., the business as usual scenario (BAU) and the integrated scenario (INT) (including three sub-scenarios, i.e., renewable energy alternatives scenario (REA), industrial structure optimization scenario (ISO) and energy saving facility scenario (ESF)). Results indicate that under the INT scenario, Zhangjiakou's greenhouse gas emissions would peak in 2030 with 13.23% of lower energy consumption when compared with the BAU scenario. Compared with the conventional energy, renewable energy shows competitive advantages in terms of greenhouse gas reduction, employment opportunities and economic costs. The total number of employees would reach 0.15 million by 2050 under the INT scenario, 1.71 times more than that in the BAU scenario. Feasible low-carbon pathways and co-benefits strategies associated with industrial transformation and renewable energy substitution should be pursued in future actionable plans. Results found in this study could provide importance information for achieving renewable energy transformation and associated socio-environmental benefits within and beyond China. Highlights: A LEAP-Zhang model is established to analyze energy-related socio-environmental dynamics. The energy-related GHG emissions are estimated for the Olympic year and peak year. The environmental, economic and employment effects of renewable energy transition are estimated. Feasible energy transition pathways are proposed for achieving socio-environmental benefits.